Ultrasonographic Prevalence and Factors Predicting Left Ventricular Diastolic Dysfunction in Patients with Liver Cirrhosis: Is There a Correlation between the Grade of Diastolic Dysfunction and the Grade of Liver Disease? - Vasilios Papastergiou; Lamprini Skorda; Phillipos Lisgos; Nikolaos Papakonstantinou; Tsampikos Giakoumakis; Konstantinos Ntousikos; Stylianos Karatapanis (The Scientific World Journal)
Presence of cardiac dysfunction has been associated with an unfavorable prognosis in patients with liver cirrhosis. In the present study, 92 consecutive, newly-diagnosed patients with liver cirrhosis were prospectively evaluated. Liver disease was graded according to the modified Child-Turcotte-Pugh (CTP) score whereas left ventricular diastolic function was assessed by Doppler-echocardiography and graded (Stage 0 to 4) according to current guidelines. Overall, DD was diagnosed in 55/92 (59.8%) patients [DD-stage-1: 36/92 (39.1%), DD-stage-2: 19/92 (20.6%)]. Prevalence of DD-stage-1 among the different stages of liver cirrhosis was: CTP-class A: 11/29 (37.9%), B: 15/39 (38.5%), C: 10/24 (41.6%), (P>0.05 in all comparisons), whereas for DD-stage-2 the corresponding proportions were CTP-class A: 3/29 (10.3%), B: 5/39 (12.8%), C: 11/24 (45.8%), (P=0.0009 between CTP-class C versus A and B). Age > 53 years (Odd’s Ratio [OR]: 4.2; 95% confidence interval [CI]: 1.5–12.1) and CTP-class C (OR: 4.6; 95% CI: 1.1–20) could independently predict DD. No relation between presence of DD and the etiology of the liver disease was found. We conclude that DD is a common feature in liver cirrhosis. DD-stage-1 is fairly prevalent among all CTP-classes whereas DD-stage-2 seems to be characteristic of the advanced liver disease (CTP-class C). A high level of awareness for the presence of the syndrome is required, especially if cirrhotic patients are CTP-class C and/or of older age.